2008
DOI: 10.1016/j.chom.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon-Induced Protein BST-2 Restricts HIV-1 Release and Is Downregulated from the Cell Surface by the Viral Vpu Protein

Abstract: The HIV-1 accessory protein Vpu counteracts a host factor that restricts virion release from infected cells. Here we show that the interferon-induced cellular protein BST-2/HM1.24/CD317 is such a factor. BST-2 is downregulated from the cell surface by Vpu, and BST-2 is specifically expressed in cells that support the vpu phenotype. Exogenous expression of BST-2 inhibits HIV-1 virion release, while suppression of BST-2 relieves the requirement for Vpu. Downregulation of BST-2 requires both the transmembrane/ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

87
1,421
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 934 publications
(1,513 citation statements)
references
References 34 publications
87
1,421
4
1
Order By: Relevance
“…In 2008, two independent laboratories showed that cell type‐specific expression of BST‐2 correlates with Vpu‐dependent release of HIV‐1. Suppression of endogenous BST‐2 expression resulted in Vpu‐independent virus release whereas rescue of expression with exogenous BST‐2 in cells that otherwise do not have high BST‐2 renders these cells Vpu‐dependent for virus release 6, 7. These findings revealed that BST‐2 is an inhibitor of virus release and a target of Vpu 6, 7.…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 93%
See 2 more Smart Citations
“…In 2008, two independent laboratories showed that cell type‐specific expression of BST‐2 correlates with Vpu‐dependent release of HIV‐1. Suppression of endogenous BST‐2 expression resulted in Vpu‐independent virus release whereas rescue of expression with exogenous BST‐2 in cells that otherwise do not have high BST‐2 renders these cells Vpu‐dependent for virus release 6, 7. These findings revealed that BST‐2 is an inhibitor of virus release and a target of Vpu 6, 7.…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 93%
“…In 2008, BST‐2 was rediscovered as the host factor responsible for preventing the release of HIV‐1 with mutated Vpu (HIV‐1 ΔVpu) from host cells 6, 7. Following these discoveries, BST‐2 was renamed tetherin 7.…”
Section: Bst‐2/tetherin: Roles In Viral Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments indicate that Vpu facilitates viral budding through interactions with host cell proteins that otherwise inhibit viral budding, 35 in particular an integral membrane protein dubbed tetherin, CD317, or BST-2. 36,37 Tetherin tethers budding virions to host cells by linking the viral and host cell membranes. 38 Vpu interferes with tetherin by targeting tetherin for degradation, in a manner similar to that by which Vpu downregulates CD4.…”
Section: Introductionmentioning
confidence: 99%
“…Vpu was classified as a class IA viroporin (Fischer et al, 2012;Luis Nieva et al, 2012). Recently it was found that Vpu antagonizes tetherin, a cellular antiviral defense factor that cross-links budding virions to the host cell membrane and thus inhibits virus release (Neil et al, 2008;Van Damme et al, 2008).…”
Section: Introductionmentioning
confidence: 99%